Palm oil mill effluent treatment using rotating biological contactor - Kassim, Mohd Azraii (Faculty of Civil Engineering, Universiti Teknologi Malaysia, 1999)
A study was conducted to treat palm oil mill effluent (POME) using a pilot scale anaerobic-aerobic rotating biological contactor (RBC). A two-stage RBC system was set up in the Environmental Engineering Laboratory at Universiti Teknologi Malaysia (UTM). The anaerobic RBC was utilised as the primary treatment unit and the effluent was further treated using an aerobic RBC. The main aims of this project were to start up the RBC system, to monitor the anaerobic and aerobic system and to investigate the ability of the unit to treat POME. After full acclimatisation, continuous flow through the system exhibited reduction efficiencies of 96%, 71% and 80% for BOD" COD and 5S respectively